Impact of Mindfulness through Smartphone Applications on the Anxiety among B.Sc. Nursing Students - A Priyadarsini; H Sangavi; J Jagadeeswari; C Cecyli; BAA Dayana (Wolters Kluwer Medknow Publications, 2024)
Smartphone addiction among undergraduate students has become a pressing concern due to its association with perceived stress levels and negative impacts on their well-being and academic performance. Quasi-experimental design with nonequivalent control group samples was 100 students. Mindfulness training by using the smartphone application in four meetings for four weeks, whereas the control group was given mindfulness training after the study in the eight weeks. Anxiety is measured by the Zung Self-Rating Anxiety Scale instrument. Data were analyzed by using Mann-Whitney and Wilcoxon tests. The study found that anxiety levels decreased after mindfulness training while in the control group, anxiety increased at posttest, indicating a significant difference. Mindfulness training through smartphone devices SIMBA application has a significant effect on reducing anxiety levels in third-year nursing students. These findings demonstrate the necessity of educating students about the detrimental consequences of smartphone addiction on mental health, especially perceived stress and promoting the adoption of coping mechanisms.